The deadly triple M (mistrust, misinformation, and missed opportunities): understanding Romania’s COVID-19 vaccination campaign and its lasting impact on public health - Dascalu, Stefan; Raiu, Catalin Valentin; Olteanu, Emilian; Comanici, Adrian Vasile; Comanici, Mihaela Maria; Toma, Tudor P.; Robu, Bogdan Ionut; Mihailov, Raul; Mina-Raiu, Laura; Dumitra, Gindrovel Gheorghe; Azoicai, Doina; Popovici, Emilian Damian; et al. (Frontiers in Public Health, 2025)
Romania’s COVID-19 vaccination campaign presents a compelling case study on the intersection of public health policy, societal dynamics, and political influences in pandemic response. Despite an initially promising rollout, Romania ultimately achieved one of the lowest vaccination rates in the European Union, with severe consequences during the subsequent pandemic waves. This review examines the key factors contributing to the campaign’s shortcomings, including pre-existing vaccine hesitancy, widespread misinformation, inadequate governmental communication strategies, and the politicisation of public health efforts. We explore the deep-seated mistrust in governmental institutions, exacerbated by restrictive measures implemented without adequate public engagement, as well as the influential role of religious communities and the rise of populist political forces that actively opposed vaccination efforts. Additionally, we discuss the impact of media sensationalism, conspiracy theories, and the failure to regulate anti-vaccine rhetoric within the medical profession. While logistical and infrastructural challenges were largely addressed, the inability to effectively engage key societal stakeholders led to lagging of vaccine uptake. The consequences of this failure extended beyond COVID-19, contributing to a severe measles outbreak in 2023, which underscored the long-term deleterious effects of vaccine hesitancy. Drawing from Romania’s experience, we highlight critical lessons for future public health campaigns, emphasising the need for trust-building initiatives, targeted misinformation countermeasures, stronger community engagement, and enhanced collaboration with religious and cultural institutions. By addressing these challenges, countries worldwide can strengthen their public health frameworks and improve the resilience of their immunisation programmes in the face of future crises.